GLOBAL TRENDS IN RELIGION AND ENTREPRENEURSHIP RESEARCH: A BIBLIOMETRIC REVIEW - Suhaida Abu Bakar; Daing Maruak Sadek; Muhammad Saiful Islami; Mohd Badrul Hakimi Daud (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This study explores the intersection of religion and entrepreneurship, examining how these domains converge to shape societal and economic landscapes. Religion, with its enduring values and ethical frameworks, profoundly influences entrepreneurial activities, serving as a moral compass and source of inspiration for many entrepreneurs. Conversely, entrepreneurship is often perceived as a means of fulfilling religious obligations, such as charity and community service. Recent research has increasingly highlighted the significant role of religion in guiding ethical decision-making, influencing business practices, and contributing to entrepreneurial success. This bibliometric review provides a comprehensive analysis of global research trends in this field, focusing on 1,387 articles published since 1966. The study employs VOSviewer software to map existing literature and identify key themes, regional focal points, and influential studies. Findings reveal that most research originates from economically developed countries, with the United States (US), the United Kingdom (UK), Indonesia, and Malaysia leading in publication output. This distribution underscores the importance of religion in shaping entrepreneurial activities across diverse cultural and economic contexts. Despite the growing academic interest, the study acknowledges certain limitations, including the reliance on the Scopus database, which may exclude relevant works from other sources. Additionally, the focus on publications from 1966 onward may overlook earlier foundational literature. This review contributes to a deeper understanding of how religion and entrepreneurship intersect, offering insights into emerging themes, gaps in the literature, and potential directions for future research.